A tunable resonant oscillating water column wave energy converter. (1st April 2016) - Liu, Chunrong
Abstract: A novel wave energy converter (UREWEC), which is constructed by attaching a U-tube to a traditional oscillating water column WEC, is proposed. To improve the performance of the UREWEC at lower wave frequencies, the two sides of the U-tube are sloped. A mathematical model based on potential theory is used to examine the wave energy extraction efficiency of the UREWEC. The analytical results show that the wave energy extraction efficiency of the UREWEC can reach 100% at the optimal frequency if the viscosity and nonlinearity are ignored. The optimal frequency of the UREWEC can be instantaneously adjusted by controlling the amount of the fluid in the U-tube and the turbine rotational speed. The sloped sides of the U-tube are beneficial to obtain a lower UREWEC optimal frequency. A smaller cross-sectional area of the U-tube can extend the adjusted ranges of the optimal frequency while increasing the wall-friction losses. Graphical abstract: Highlights: A novel wave energy converter was proposed by attaching a U-tube to a traditional OWC. The presented wave energy converter can absorb all wave enegy for a given frequency. The high-efficiency frequency band can be widened by adjusting the parameters of the U-tube.